A proposed program of the high school [Ifugao Academy] for the improvement of Ifugao economy - Uyan, Venancio T. 1918- (s.n.], 1958)
This is a study of the economic conditions, problems and needs of a rural community and the program of a general high school. It aims at formulating a proposed program of the high school for the improvement of the economy of the community.